2012
DOI: 10.1016/j.jpsychires.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of spontaneous improvement to placebo response in depression: A meta-analytic review

Abstract: Objectives It is unknown to what degree spontaneous improvement accounts for the large placebo response observed in antidepressant trials for Major Depressive Disorder (MDD). The purpose of this study was to estimate the spontaneous improvement observed in treatment-seeking individuals with acute MDD by determining the symptom change in depressed patients assigned to wait-list controls in psychotherapy studies. Method The databases PubMed and PsycINFO were searched to identify randomized, prospective studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…A meta-analytic comparison of head-to-head trials and placebo-controlled trials of the same drugs for treating depression demonstrated that comparative trials enhance the drug response compared with placebo-controlled trials of the same compounds. This effect is explained solely by the patient's 100% assurance to receive a drug, and it resulted in an additional 15% "placebo response" to the established average of 40% from placebo-controlled drug trials for depression (Rutherford et al, 2012). Similar data have been reported in schizophrenia (Woods et al, 2005).…”
Section: Head-to-head Trials: No Placebo Arm But Even Stronger Plamentioning
confidence: 60%
See 1 more Smart Citation
“…A meta-analytic comparison of head-to-head trials and placebo-controlled trials of the same drugs for treating depression demonstrated that comparative trials enhance the drug response compared with placebo-controlled trials of the same compounds. This effect is explained solely by the patient's 100% assurance to receive a drug, and it resulted in an additional 15% "placebo response" to the established average of 40% from placebo-controlled drug trials for depression (Rutherford et al, 2012). Similar data have been reported in schizophrenia (Woods et al, 2005).…”
Section: Head-to-head Trials: No Placebo Arm But Even Stronger Plamentioning
confidence: 60%
“…A meta-analysis of three-arm trials in 8 different clinical conditions including a "no treatment" control group revealed that about 50% of the placebo response could be explained by spontaneous remission/ variation (Krogsboll et al, 2009). Although only involving 10 trials, a similar meta-analysis in major depression disorder (Rutherford et al, 2012) indicated that "waiting" had an effect size of approximately 0.5 (Cohen's d), the equivalence of a 4-point, clinically relevant improvement on the Hamilton Depression Scale. However, a waiting list is a poor means of "no treatment control" because it induces a dynamic (the expectation of being treated in the near future) that differs from that in an observation study arm only (Relton et al, 2010).…”
Section: A Effect Sizes Of Symptom Improvement Across Different Medimentioning
confidence: 99%
“…Taken together, these results could indirectly imply an awareness of expressions such as "probability" and "placebo" in studies with children too, although it cannot be excluded that it depends more on reactions of parents as stated above. However, crossover trials-although they also provide a 100% chance of receiving active treatment-have another pitfall that may corrupt proper estimation of drug and placebo effects: patients who receive the drug first and then the placebo may show higher placebo response rates (due to conditioned drug effects from the first treatment phase) (48) than those who receive the placebo first and then the drug-the latter may "profit" from the natural course of disease that frequently occurs in acute medical conditions (49) but is incorrectly attributed to the drug effect.…”
Section: Are the Mechanisms Underlying The Placebo Effect Similar Betmentioning
confidence: 99%
“…That is, for the buddy-MI group the change was seen as early as one-month but for the control group it was three-months before significant change from baseline was seen. It is known that spontaneous improvement accounts for some of the response observed in wait-list participants in psychological trials (Rutherford, Mori, Sneed, Pimontel, & Roose, 2012). Participants can acutely experience improvement even without treatment.…”
Section: Discussionmentioning
confidence: 99%